Sexual Health Education in Obstetrics and Gynecology (Ob-Gyn) Residencies—A Resident Physician Survey. Issue 6 (18th May 2021) - Worly, Brett; Manriquez, Maria; Stagg, Amy; Blanchard, May Hsieh; Ogburn, Tony; Carson, Sandra Ann; Woodland, Mark B.
ABSTRACT: Background: Many women will experience a sexual health concern and present to their Obstetrics and Gynecology (Ob-Gyn) care provider, yet a large portion of graduating Ob-Gyn resident physicians in the United States may not feel comfortable helping patients with some sexual health issues. Aim: To perform a cross-sectional study of U.S. Ob-Gyn resident physicians that assesses sexual health education didactic sessions and comfort level with sexual health clinical vignettes. Methods: A 32-item anonymous survey was sent to all 4, 065 Ob-Gyn residents on June 7, 2016. Respondents voluntarily completed the survey electronically. Outcomes: The primary outcome measures are the comfort level of Ob-Gyn resident physicians in taking a sexual history and providing counseling to patients represented in clinical vignettes, which were based on sexual health learning objectives from the Council on Resident Education in Obstetrics and Gynecology (CREOG). RESULTS: Of the 4, 065 eligible U.S. examinees, 968 (23.8%) agreed to participate in the study, and 802 (19.7%) completed the survey and were included in the final analysis. Nearly two-thirds of the residents indicated that sexual health training was a priority in residency. However, more than half were not able to describe the disorders of sexual function or list common medications that effect sexual function. When posed with clinical vignettes, residents felt very comfortable obtaining a sexual history (98.5%) and providing counseling (97.0%) for a 16-year-old seeking contraception, yet fewer felt very comfortable obtaining a history and providing counseling for a 26-year-old who is a refugee from Somalia (77.2% and 73.8%). Smaller cohorts felt prepared to take a sexual history and provide counseling for a 17-year-old who discloses that she is a victim of sex trafficking (61.2% and 57.7%), and for a 58-year-old transgender patient planning hormone therapy and surgery (49.9% and 37.9%). In logistic regression analysis, the factors that were influential in an Ob-Gyn resident physician's program to prepare them to describe the disorders of sexual function were post-graduate year (OR 1.387, 95% CI 1.189, 1.618; P = .0001), those that rated the importance of a sexual health curriculum highly (OR 0.701, 95% CI 0.569, 0.864; P = .0012), and a greater number of didactic sessions on sexual health in the residency curriculum (OR 0.685, 95% CI 0.626, 0.750; P < .0001). CONCLUSION: These findings highlight strengths in the comfort of Ob-Gyn resident physicians about sexual health and illustrate areas of opportunity to engage resident learners by improving the sexual health curriculum.